Efektivitas Night Guard dalam Menurunkan Tooth Wear dan Implikasi terhadap Performa Atlet Bulu Tangkis: Tinjauan Literatur - Cindy Hendrawan; Sheryn Marcha Ramaniasari; Dian Samuel Hasudungan; Nurul Hidayati; Yessy Andriani Fauziah; Eveline Yulia Darmadi (Universitas Al Azhar Indonesia, 2026)
Tooth wear is a progressive loss of dental hard tissue commonly associated with parafunctional activities such as bruxism and clenching. In badminton athletes, physiological and psychological stress during training and competition may increase sleep bruxism activity, thereby accelerating occlusal surface wear and disrupting the stomatognathic system. The use of night guard or occlusal splint has been recommended as a conservative therapy to stabilize occlusal force distribution, reduce destructive tooth contact and decrease masticatory muscle hyperactivity during bruxism episodes. This literature review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach to evaluate the effectiveness of night guard use in reducing tooth wear and to examine its implications for focus and concentration in badminton athletes within the field of sports dentistry. Literature searches were performed through PubMed, Scopus, ScienceDirect and Google Scholar for articles published between 2020 and 2025. The findings indicate that night guards are effective in reducing bruxism activity, minimizing excessive occlusal load and providing protective effects on enamel and dentin. Occlusal stabilization may also influence neuromuscular function and athletic performance readiness. However, evidence regarding its direct effects on athletes’ focus and concentration remains limited and requires further investigation.Keywords – Bruxism, Night Guard, Tooth Wear.